Thermo-mechanical characterization of polyimide thin film using bulge test - Mehul Mukund Vora (2014)
Bulge test has been used to test elastic properties of metal and ceramic films, but has proved inadequate to the task of testing viscoelastic properties for materials like polymers. A novel bulge test setup has been designed to overcome this drawback. The capability of the new setup to test at elevated temperatures and in controlled environments increases the scope of bulge test to a wide range of tests and materials. PMDA-ODA polyimide is used as the material to be characterized using the new bulge test setup designed as part of the dissertation. The material is also tested with alternative testing methods (TGA, TMA, wafer curvature and microtensile). The results from the alternate methods are used in conjunction to confirm the findings of bulge test as well as to prove its validity as a viscoelastic characterization tool. The polyimide material is characterized for it Tg, degradation temperature, coefficient of thermal expansion, residual stress, modulus and creep behavior.